A Watershed Approach to Co-Creating Just Sustainabilities: Reflections from the Lake Superior Living Labs Network - Charles Z. Levkoe; Nairne Cameron; Lindsay P. Galway; Rachel L. W. Portinga; Randy Hanson; Kathryn Milun; Erika Vye (Interdisciplinary Journal of Partnership Studies)
Campus-community partnerships are well-positioned to play a role in advancing social and environmental justice in the context of our rapidly changing and increasingly inequitable world. Across the Global North, post-secondary institutions, civil society organizations, and communities are partnering to establish living labs by integrating research, teaching, and community engagement to advance regenerative social-ecological systems. Living labs aim to co-create innovative solutions to complex challenges through interdisciplinary, placed-based experiential learning and community-engaged action in the built and natural environments. In this paper, we focus on the potential for living labs to establish connections between people and communities and increasing the impact of place-based activities focused on social and environmental justice and sustainability, also known as just sustainabilities. We reflect on our collective experiences working with the Lake Superior Living Labs Network (LSLLN), a nested network of living labs collaborating across the Lake Superior watershed. The LSLLN was established in 2018 as a platform to connect academics and community groups across Canada, the United States, and multiple Indigenous territories, with the goal of developing and expanding partnerships and place-based collaborative initiatives grounded in the Lake Superior watershed as a social-ecological system. Drawing on these insights, we consider the possibilities for a watershed-based approach to living labs. We conclude with a discussion that suggests that nested and networked living labs have the potential to enhance relationships and increase the impact of place-based social justice and sustainability-related activities, while pointing to several limitations of working within existing institutional structures.